2008
DOI: 10.1016/j.molmed.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The complex role of B7 molecules in tumor immunology

Abstract: T-cell activation requires the interaction of the T-cell receptor with a cognate major histocompatibility complex (MHC)-peptide complex. Initiated by antigen engagement, the adaptive immune response is orchestrated by a complex balance between stimulatory and inhibitory signals that are predominantly controlled by members of the B7 family. Here, we review the current knowledge on B7 family members concerning their constitutive and regulated expression, modulation of the immune response and their role in the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 113 publications
1
67
0
Order By: Relevance
“…42 However, almost none of the relevant review articles include BTLA as a B7-H4 receptor. 10,[43][44][45][46][47][48][49][50] Our findings provide additional support for the role of BTLA as a B7-H4 receptor.…”
Section: Discussionsupporting
confidence: 61%
“…42 However, almost none of the relevant review articles include BTLA as a B7-H4 receptor. 10,[43][44][45][46][47][48][49][50] Our findings provide additional support for the role of BTLA as a B7-H4 receptor.…”
Section: Discussionsupporting
confidence: 61%
“…Expression of the important costimulatory molecule CD80 on antigen-presenting cells enhances the activation of naïve T cells (52) and is up-regulated by both CD40 and LMP1 (3,22). Previous studies revealed that CD40 does not require the TRAF6 TRAF-C domain to induce CD80 expression in B cells (29).…”
Section: Tantly Traf6mentioning
confidence: 99%
“…The second signal is provided by the interaction between CD28 on the T cell surface and CD86 (B7-1) or CD80 (B7-2) on the APCs (Alegre et al, 2001;Handa et al, 2005). This co-stimulatory signal leads to clonal-T lymphocytes expansion and differentiation and to cytokines expression (Melichar et al, 2000;Seliger et al, 2008). In fact, the ligation of CD28 and CD3 (a T cell coreceptor) promotes the production of interleukins IL-4 and IL-5 and seems to be unique in its ability to induce very high levels of IL-2 production by prolonging the nuclear residency of nuclear factor of activated T cells (NFAT).…”
Section: Costimulatory Molecules Pathway Of T Lymphocytes Activationmentioning
confidence: 99%